Data Mesh Architecture: Revolutionizing Enterprise Data Management through Decentralization - Arun Vivek Supramanian (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article provides a comprehensive exploration of Data Mesh Architecture, a revolutionary approach to data management that addresses the limitations of traditional centralized systems. We delve into the core principles of Data Mesh, including domain-oriented data ownership, self-serve infrastructure, federated governance, and treating data as a product. The article compares Data Mesh with traditional data warehouses and data lakes, highlighting its advantages in scalability, reduced dependency on central IT teams, and faster decision-making. We examine enabling technologies such as Apache Iceberg, Delta Lake, Snowflake, and AWS S3, discussing their roles in facilitating data discoverability, versioning, and governance. Real-world case studies from large organizations demonstrate the practical implementation and benefits of Data Mesh. The article also addresses the challenges in adopting this architecture, including necessary cultural shifts, data standardization issues, and security considerations. Finally, we offer best practices for organizations considering Data Mesh adoption, emphasizing the importance of organizational readiness assessment, phased implementation, and ongoing training and skill development. This comprehensive article serves as a valuable resource for data professionals and business leaders seeking to modernize their data architecture and unlock the full potential of their data assets.